2018
DOI: 10.1186/s13063-018-3066-9
|View full text |Cite
|
Sign up to set email alerts
|

Stopping or maintaining oral anticoagulation in patients undergoing photoselective vaporization of the prostate (SOAP) surgery for benign prostate obstruction: study protocol for a multicentre randomized controlled trial

Abstract: BackgroundLower urinary tract symptoms related to benign prostatic obstruction (BPO) are frequent in men aged > 50 years. Based on the use of innovative medical devices, a number of transurethral ablative techniques have recently been developed for the surgical treatment of BPO. In recent years, GreenLight photoselective vaporization of the prostate (PVP) has been considered as a non-inferior alternative to transurethral resection of the prostate. The GreenLight PVP is usually considered as an interesting surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Greenlight has also been shown to have lower bleeding complication rates when compared to TURP (78). RCTs are currently being designed to further study the use of Greenlight in those patients taking anticoagulants (79). A multicenter RCT reported that Greenlight 120-W had comparable uroflowmetry parameters and complications with TURP but had significantly lower length hospital stays for patients (80).…”
Section: Holmium Laser Enucleation Of the Prostate (Holep)mentioning
confidence: 99%
“…Greenlight has also been shown to have lower bleeding complication rates when compared to TURP (78). RCTs are currently being designed to further study the use of Greenlight in those patients taking anticoagulants (79). A multicenter RCT reported that Greenlight 120-W had comparable uroflowmetry parameters and complications with TURP but had significantly lower length hospital stays for patients (80).…”
Section: Holmium Laser Enucleation Of the Prostate (Holep)mentioning
confidence: 99%
“…Knapp et al published a study comparing adverse events amongst patients undergoing PVP. 26 This study contained 59 patients taking anticoagulants and 42 patients taking aspirin while undergoing PVP and compared against a control group of 272 patients. This study also highlighted the low bleeding risk associated with PVP, with only one patient from each of the aspirin and anticoagulant groups requiring readmission due to haematuria/clot retention.…”
Section: Discussionmentioning
confidence: 99%